PLEA BARGAINING DALAM RANCANGAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA NEGARA INDONESIA - Alimuddin, Alimuddin; Zahir, Muh Zuhud Al-Khaer; Rasyid, Muh Firdaus; Hastira, Muh Fichriyadi (Universitas Muhammadiyah Ponorogo, 2024)
The purpose of this study is to evaluate the legal political structure and the level of urgency of the Plea Bargaining System in the Draft Criminal Procedure Code. Normative legal research is the type of research used. The study of legal issues relating to norms is emphasized in legal research techniques. This method will concentrate on looking at legal reality from the point of view of the legal substance that regulates and is still developing. The findings of this study indicate that the Plea Bargaining system in the Draft Criminal Procedure Code is needed. This is indicated by the fact that several countries, such as Germany and France, have successfully implemented similar systems with various models and techniques. However, the Plea Bargaining system in the Draft Criminal Procedure Code does not use these strategies, but rather emphasizes that Plea Bargaining is only to alleviate the charges and accelerate the trial process. Plea Bargaining is expected to accelerate the legal process by reducing the volume of cases brought to court, saving time and money, compensating defendants who admit their guilt, and meeting the needs of the public prosecutor and defendants. With the establishment of the Special Track, Article 199 of the Draft Criminal Procedure Code describes the form of the Plea Bargaining system in its application and offers the idea of a Plea Bargaining system with a maximum penalty of 7 years as one of the options in accelerating case settlement. The use of Plea Bargaining has several advantages as follows: one, it reduces the accumulation of cases in court; two, it provides relief for defendants who admit their guilt; and the third simplifies the process for public prosecutors.